External Morphological Study of Apantesis Carlotta Ferguson, 1985 Arctiidae-Lepidoptera-Insect in Baghdad, IRAQ - Wahhab Azooz, Hayder; Jammel Sabr, Ahmed (Journal of Neonatal Surgery, 2025)
Apantesis carlotta Packard, 1985, a species of moth belonging to the family Arctiidae within the order Lepidoptera, was identified in Baghdad, Iraq. This species is distinguished from others in its family based on its geographical distribution and morphological features, particularly those related to reproductive organs. As an arthropod of economic significance, the Arctiidae family is notable for its larvae, some of which are characterized by their hairy appearance. Fieldwork was carried out in various locations across Iraq, a country rich in biodiversity, from April 2023 to March 2024. Specimens were collected using air nets and fluorescent lights at night from mulberry trees and clover plants. The collected samples were preserved in plastic containers with 70% ethyl acetate. The species were identified, compared with existing taxonomic keys, and newly documented species were given formal taxonomic descriptions. Morphological classification was achieved by focusing on specific phenotypic traits and photographing the specimens using a mobile camera.